2015
DOI: 10.1002/anie.201503319
|View full text |Cite
|
Sign up to set email alerts
|

Aryne‐Induced Novel Tandem 1,2‐Addition/(3+2) Cycloaddition to Generate Imidazolidines and Pyrrolidines

Abstract: A new "single-flask" method was developed for the synthesis of imidazolidines and pyrrolidines with high stereoselectivity. First, a Schiff base was arylated with an aryne. Second, an intramolecular proton transfer took place from the methylene position to the anionic aryne ring. Third, the resultant ylide reacted with a second equivalent of the same Schiff base in situ or an electron-deficient alkene through a (3+2) cycloaddition. These sequential tandem 1,2-addition/(3+2) cycloaddition reactions led to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In addition, imidazolidines 189 were analogously obtained adding 2 equiv of imino ester 107 under mild conditions (Scheme 55). 81 Both types of heterocycles were tested as antiviral agents, specifically to those emerging viral infections.…”
Section: Scheme 53 Stereoselective Synthesis Of Triazolobenzodiazepinesmentioning
confidence: 99%
“…In addition, imidazolidines 189 were analogously obtained adding 2 equiv of imino ester 107 under mild conditions (Scheme 55). 81 Both types of heterocycles were tested as antiviral agents, specifically to those emerging viral infections.…”
Section: Scheme 53 Stereoselective Synthesis Of Triazolobenzodiazepinesmentioning
confidence: 99%
“…For example, Yoshida and co‐workers [7] invent a method for the synthesis of benzoxazinones by treating benzyne with Schiff bases in the presence of CO 2 . Our group [8] find that arynes react with two equivalents of Schiff bases to produce imidazolidines. Furthermore, reaction of arynes with one equivalent of Schiff bases in the presence of electron‐deficient alkenes generates pyrrolidines [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Our group [8] find that arynes react with two equivalents of Schiff bases to produce imidazolidines. Furthermore, reaction of arynes with one equivalent of Schiff bases in the presence of electron‐deficient alkenes generates pyrrolidines [8] . Jugé et al [9] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2006 H. Yoshida and co‐workers demonstrated the ability to access benzoxazinones 5b via trapping of the 1,3‐zwitterion by carbon dioxide using imines in which the carbon‐bound group is an alkyl moiety. In 2015 Hwu et al showed the diastereoselective formation of imidazolidines 5a and other N ‐heterocycles via trapping of the intermediate 1,3‐dipole 3e , formed via intramolecular proton transfer within 3a . Finally, in 2017 researchers in the Tian laboratory showed that 3a may be trapped by protic carbon nucleophiles in a three‐component fashion to form products of the type 5c .…”
Section: Introductionmentioning
confidence: 99%